Hubungan Derajat Acne Vulgaris dengan Tingkat Ansietas pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Ni Putu Ardiya Widasari; Sri Agung Aryastuti Anak Agung; I Gde Nengah Adhilaksman Sunyamurthi Wirawan (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[The Relationship between the Degree of Acne Vulgaris and the Level of Anxiety in Medical and Health Sciences Students of Warmadewa University] Acne vulgaris is the 8th highest disease in the world, with a prevalence of about 94% of the global population. According to the Global Burden of Disease (GBD) study, 85% of adolescents and young adults aged 12 to 25 years have the problem of Acne vulgaris. Acne vulgaris is one of the diseases of the skin with inflammation in the Pilosebaceous unit. The onset of Acne vulgaris can cause discomfort and a disturbance in an individual's realistic assessment of himself. This is what can trigger a sense of anxiety. The purpose of this study is to find out whether there is a relationship between the degree of Acne vulgaris and the level of anxiety in students of the Faculty of Medicine and Health Sciences, Warmadewa University. This study uses a quantitative approach through a cross-sectional design. The sampling technique of this study was carried out using the purposive sampling method. The research instrument used was the Hamilton Anxiety Rating Scale (HARS) questionnaire as a benchmark to assess the level of anxiety and Lehmann's classification to determine the severity of Acne vulgaris. Data processing was carried out by bivariate analysis using the Spearman correlation test. This study involved 63 respondents. Most of the respondents were women (25.4%), 18 years old (52.4%), experiencing mild Acne vulgaris (68.3%) and mild anxiety (41.3%). From the results of the analysis, it was found that the relationship between the degree of Acne vulgaris and the level of anxiety in students of the Faculty of Medicine and Health Sciences, Warmadewa University (p = 0.001; r = 0.650). For the next research, it is recommended to be able to improve and improve the results of the research by looking for information related to other factors besides Acne vulgaris that can cause anxiety in medical students.